Component 1 Inhibitor Missense (Val480Met) Variant Is Associated With Gene Expression and Sepsis Development in Neonatal Lung Disease - Elngar, Enas F.; Azzam, Mona A.; Gobarah, Ayman A.; Toraih, Eman A.; Fawzy, Manal S.; AbdAllah, Nouran B. (Frontiers in Pediatrics, 2022)
Background: Neonatal lung disease has a multifaceted etiopathology, including an explosive inflammatory sequence in the immature lung. Complement component 1 Esterase INHibitor (C1INH) is implicated in controlling inflammation in response to infection/injury. Aim: To explore for the first time the association of the C1INH rs4926 (Val480Met) variant and circulatory transcript expression levels in the neonates that had evidence of lung disease and the clinic-laboratory data. Methods: A total of 139 unrelated neonates were enrolled in this case-control study. C1INH genotyping and expression analyses were done using TaqMan Genotyping and Real-Time qPCR, respectively. Results: A/A genotype carriers were two times more likely to develop in newborns with lung disease under homozygote (A/A vs. G/G: OR=2.66, 95%CI=1.03-6.87, p=0.039) and recessive (A/A vs. G/G-A/G: OR=2.42, 95%CI=1.07-6.06, p=0.047) models. Also, a higher frequency of A/A genotype was observed in the patient’s cohort complicated with sepsis (44.2% vs. 14.3%, p=0.002). Neonates with lung disease with A variant had more risk for developing sepsis under homozygote (A/A vs. G/G: OR=5.19, 95%CI=1.73-15.6, p=0.002), dominant (A/G-A/A vs. G/G: OR=2.39, 95%CI=1.02-5.58, p=0.041), and recessive (A/A vs. G/G-A/G: OR=5.38, 95%CI=1.86-15.5, p<0.001) models. Regression analysis revealed rs4926*A/A genotype as an independent predictor risk factor for sepsis development in cohorts with lung disease (adjusted OR=4.26, 95%CI=1.38-13.1, p=0.012). The circulatory transcript was significantly downregulated in neonates with lung disease in whom rs4926*A/A carriers had the least expression levels (median: -2.86, IQR: -3.55 to -1.71; p<0.001). ROC curve analysis revealed C1INH expression could differentiate between cohorts with/without subsequent development of sepsis, and the discrimination ability was enhanced when combined with circulatory IL-6 and CRP levels (AUC=0.926, 95%CI=0.87-0.97). Conclusion: The C1INH rs4926 variant might play an essential role in the susceptibility to neonatal lung disease and could predict sepsis development in this cohort. Furthermore, the circulatory expression levels of this gene were downregulated in the neonatal lung disease cohort, supporting its potential role in the pathophysiology of this disorder, and highlighting its promising role in future targeted therapy.